Synthesis of Aromatic Thiolate-Protected Gold Nanomolecules by Core Conversion: The Case of Au 36 (SPh- t Bu) 24 - Theivendran, Shevanuja; Dass, Amala (Langmuir, 2017)
Ultrasmall nanomolecules (<2 nm) such as Au (SCH CH Ph) , Au (SCH CH Ph) , and Au (SCH CH Ph) are well studied and can be prepared using established synthetic procedures. No such synthetic protocols that result in high yield products from commercially available starting materials exist for Au (SPh-X) . Here, we report a synthetic procedure for the large-scale synthesis of highly stable Au (SPh-X) with a yield of ∼42%. Au (SPh-X) was conveniently synthesized by using tert-butylbenzenethiol (HSPh-tBu, TBBT) as the ligand, giving a more stable product with better shelf life and higher yield than previously reported for making Au (SPh) from thiophenol (PhSH). The choice of thiol, solvent, and reaction conditions were modified for the optimization of the synthetic procedure. The purposes of this work are to (1) optimize the existing procedure to obtain stable product with better yield, (2) develop a scalable synthetic procedure, (3) demonstrate the superior stability of Au (SPh-tBu) when compared to Au (SPh) , and (4) demonstrate the reproducibility and robustness of the optimized synthetic procedure.